The chromodomain helicase Chd4 is required for Polycomb-mediated inhibition of astroglial differentiation - Sparmann, Anke; Xie, Yunli; Verhoeven, Els; Vermeulen, Michiel; Lancini, Cesare; Gargiulo, Gaetano; Hulsman, Danielle; Mann, Matthias; Knoblich, Juergen A; van Lohuizen, Maarten (The EMBO journal, 2013)
Polycomb group (PcG) proteins form transcriptional repressor complexes with well‐established functions during cell‐fate determination. Yet, the mechanisms underlying their regulation remain poorly understood. Here, we extend the role of Polycomb complexes in the temporal control of neural progenitor cell (NPC) commitment by demonstrating that the PcG protein Ezh2 is necessary to prevent the premature onset of gliogenesis. In addition, we identify the chromodomain helicase DNA‐binding protein 4 (Chd4) as a critical interaction partner of Ezh2 required specifically for PcG‐mediated suppression of the key astrogenic marker gene GFAP . Accordingly, in vivo depletion of Chd4 in the developing neocortex promotes astrogenesis. Collectively, these results demonstrate that PcG proteins operate in a highly dynamic, developmental stage‐dependent fashion during neural differentiation and suggest that target gene‐specific mechanisms regulate Polycomb function during sequential cell‐fate decisions. The Polycomb Group (PcG) transcriptional repressor complex interacts with Chd4 to suppress the astrogenic marker GFAP, thereby preventing premature gliogensis during neocortical development.